The researcher - entrepreneur: crossing (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
This article aims to present the results of a research conducted in the metropolitan area of the district of Barranquilla (Colombia), directed to investigate and characterize the profile of the researcher-entrepreneur, regarding the motivating factors, conditions of the environment, development and implementation, factors of success or failure and its social, economic and Knowledge impact. The methodology used was a study of exploratory-descriptive character; an instrument was developed to survey researchers from universities and institutes of technical and technology education. With some experience in technology transfer processes, this work was accompanied by a comparative study the state of art of the profiles of the researchers both nationally and internationally. Among the results found the following characteristics were the common denominator of the profiles: leadership, communication skills, proper handling of technology transfer, proper inter-and intrapersonal handling of information, adequate handling of time, teamwork, identification and use of networks and contacts. Furthermore, it was found that it is necessary that universities provide the right conditions to promote and allow for adequate development of researcher-entrepreneurs, accompanied from motivation to consulting in business management. In conclusion we can say that, to transcend the frontiers of research to entrepreneurship, a strong motivation is required from the investigator, a clear process technology management, backup and parameters clear institutional, convinced that the process is attainable.
Keywords: entrepreneurship; researchers; entrepreneurial profile; spin off